The Influence of Leadership Style and Employee Retention on Job Satisfaction with Organizational Citizenship Behavior as a Moderation Tool at PT Pelindo Multi Terminal Branch Lhokseumawe - Taufik Rahmat Nasution; Yohny Anwar; Kiki Farida Ferine (Utan Kayu Publishing, 2026)
This study aims to analyze the influence of leadership style and employee retention on job satisfaction with Organizational Citizenship Behavior (OCB) as a moderation variable at PT Pelindo Multi Terminal Branch Lhokseumawe. The approach used is quantitative associative research. The population in this study is all employees of PT Pelindo Multi Terminal Branch Lhokseumawe which totals 40 people, with sampling techniques using saturated sampling. Data was collected through questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS. The results of the measurement model test showed that all research indicators met the criteria of validity and reliability. The structural model has strong predictive capabilities, which is indicated by the R² values of job satisfaction and OCB in the high category, as well as the values of Q² and Goodness of Fit (GoF) which indicate that the model has excellent feasibility and predictability. The results of the direct relationship test showed that leadership style and employee retention had an effect on OCB, but both had not a direct effect on employee job satisfaction. In addition, OCB has also not had a direct effect on job satisfaction. Testing the effect of moderation showed that OCB was unable to moderate the relationship between leadership style and employee retention and job satisfaction.